Możliwości ograniczenia monopolu w lokalnym transporcie zbiorowym w Kielcach - Stachowicz, Monika (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Gminas are the basic units of local government in Poland, responsible for local services. One of such services is a local public transport. Despite of the direct provider it is the gmina who has to organize and control the services. Local public transport is susceptible for marketizing because of relatively law barriers for competitions on the one hand and to easy supervision over complying the standards on the other. Choosing the best provider for local services is posible through the adjudication proces. In practice, however, a replacement of the hitherto monopolist by a new contractor may become difficult. An example presented in the paper reveals the lack of elasticity in preparing the adjudication procedures what made the local monopolist even stronger. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 442-449